POTRET PETANI MUDA (Kasus Pada Petani Muda Komoditas Hortikutura di Kabupaten Bandung Barat) - Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa (JURNAL AGRIBISAINS, 2019)
BPS data shows a decrease in the number of people working in the agricultural sector and the age structure of farmers is dominated by older farmers. The decline in the number of farmer households in Indonesia is caused by several factors, including death or moving out of the agricultural sector, and on the other hand there are fewer new residents involved in the agricultural sector. However, an interesting phenomenon in West Bandung Regency is that horticulture farming is beginning to be sought after by young farmers. This study aimed to provide an overview of young farmers analyzed through the characteristics, perceptions, and background of young farmers in running horticulture farming in West Bandung Regency. This research was a quantitative research with survey techniques. Respondents in this study were 120 young farmers who were randomly selected. Data were analyzed descriptively. The results showed that there were still a few young farmers who were college graduates, have the land of <0.5 ha and not long enough to run farming. Most young farmers have parents who also work as farmers. The main factor that drives young farmers to engage in agriculture were parental and evirontment support and quite promising opportunities in the horticulture sub-sector. Keywords : Farmer, Young, Horticulture